3D numerical simulation of the cracking behaviour of a RC one-way slab under the combined effect of thermal, shrinkage and external loads - Gomes, José Guimarães (2020)
Cracking control of reinforced concrete (RC) is of paramount importance to ensure a proper service behaviour on RC structures, during their lifespan, without excessive maintenance costs. Current design codes and recommendations for RC structures provide methodologies for reinforcement design on elements subjected to the independent effects of either external loads or restraints due to imposed deformations. However, the determination of restraint forces and crack width control in structures subjected to the combination of such two effects is still a challenge, due to the lack of knowledge about the complex interplay between the effect of bending, viscoelasticity and imposed deformations on crack width development. In this paper, the serviceability behaviour of a restrained one-way slab, subjected to a quasi-permanent load combination, is simulated with a 3D thermo-hygro-mechanical analysis. In this multi-physical approach, which has been cumulatively implemented and validated by this research team over the last years, the thermal and moisture fields of the slab are determined based on a thermo-hygrometric analysis, and the non-uniform distribution of stresses caused by selfimposed deformations due to heat of hydration and drying shrinkage are taken into account in a structural nonlinear mechanical model. Results show that the axial restraint force acting on the slab is significantly smaller than the cracking force of the slab if analysed under pure tension. This is caused by bending stresses, as well as self-imposed non-uniform stresses, and is in line with the current state of the art. However, a comparison with simplified approaches, where the effect of heat of hydration is disregarded and/or a uniform moisture field is considered, shows significant differences in behaviour until crack stabilization, in relation to the multi-physical approach presented and adopted in this work.